Prospect and sustainability of property development on highland and steep slope areas in Selangor-Malaysia: Reexamining of regulations and guidelines - Alias, A.; Othman, K.N. (2012)
Governing property development has always requires a holistic approach in decision making. The legislations for property development that are in placed still could not ensure the sustainability of development pertinently on highland and steep slope areas. These areas need more detail consideration and approaches specifically in the development process, implementation as well as the monitoring aspect. In lieu of that, the current planning, development guidelines and regulations have been evaluated as to examine the effectiveness of the current development mechanism in ensuring sustainable highland and steep slope development. Evidences from the case study have shown that the weaknesses lie in the decision making process, implementation and enforcement aspect of the property development process which have high influence in the property development growth and values. Besides, the study also revealed that property legislation setting should provide the implementation mechanism. Recommendations to ensure the prospect and sustainability of high land and steep slope development are emphasis on the needs in continuation of legislations and implementation procedures, monitoring actions as well as the necessity for the development players to collaborate and understand the important of sustainable development.